Efforts to Improve Children's Motor Skills and Creativity Through Activities at The Center for Natural Materials - Rahmah Rahmah; Zainal Abidin; Ibdalsyah Ibdalsyah (Universitas Al-Hikmah Indonesia, 2025)
This classroom action research aims to improve children's motor and creativity skills through activities in the natural materials center at TK Kesuma Bangsa, Sukabumi. The research was conducted in three cycles, each consisting of two meetings and involving 14 children in group A. Data collection methods included observation and documentation. In the pre-cycle stage, both motor and creativity skills were still in the